Review on Polyurethane Solubilization in Deep Eutectic Solvents (DES) for Plastic Recycling - Mohd Razib, Amirah Nasuha; Md Sarip, Mohd Sharizan; Nik Daud, Nik Muhammad Azhar; Jainoo, Ishak (TECHNO-SOCIO EKONOMIKA, 2025)
Deep eutectic solvents (DES) are a novel category of environmentally friendly solvents created by the interaction of hydrogen bond donors (HBDs) and acceptors (HBAs) in precise molar ratios, exhibiting unique physicochemical characteristics. DES have low volatility, non-flammability, and great stability, making them ecologically benign substitutes for traditional solvents. The essential physical qualities of DES, including density, viscosity, and thermal stability, are pivotal to its operation. These characteristics are affected by parameters like as temperature, component mix, and molar ratios, enabling customisation for particular purposes. DES have shown considerable promise in several domains, including electrochemistry, material synthesis, and environmentally friendly chemical processes, owing to their adaptability and safety. In the realm of polyurethane (PU) solubilisation, deep eutectic solvents (DES) have notable potential. The solubilization process is ascribed to the breakdown of the polymer’s hydrogen bonds and the dissolving of urethane connections by the DES components, helped by their strong hydrogen bond network. By customising DES characteristics, researchers may enhance the breakdown process for PU, offering a sustainable solution to plastic waste issues. The basic features, physical and chemical properties, wide range of uses, and potential for developing PU solubilisation technologies of DES are highlighted in this paper.